Development of dual X-mode Doppler reflectometry system in Heliotron J. (1st May 2022) - Kondo, Y.; Ohshima, S.; Kuwahara, D.; Inoshita, K.; Fukuda, T.; Minami, T.; Kado, S.; Kobayashi, S.; Konoshima, S.; Mizuuchi, T.; Okada, H.; Tomita, T.; et al.
Abstract: A dual X-mode Doppler reflectometry system is developed to measure the radial electric field in a stellarator/heliotron device, Heliotron J. The system is designed to have dual channels where the observation points are placed symmetrically to the equatorial plane, enabling the poloidal flow velocity measurement at two different positions in the same toroidal section, which is useful for the search for a zonal flow. In the system, an RF source generates the microwave frequency of 8.25–12.5 GHz, upconverted by an intermediate frequency of 27.5 MHz and transmitted with a coaxial cable to a transmitter located near the Heliotoron J vacuum vessel. After quadrupling the RF waves at the transmitter, the microwaves of 33–50 GHz are injected in X-mode into a plasma using a spherical focusing mirror installed inside the vacuum vessel. The local wavenumber of the probing microwaves, k ⊥, is 1.56–1.66 cm −1 . The Doppler-shifted reflected wave is downconverted to a 110 MHz signal by mixing with the LO at the receiver, amplified, and then detected by an I / Q detector. In a tabletop test, we have confirmed that the phase estimated by the I / Q detector is proportionally changed as a function of the horn antenna distance. We have successfully measured the Doppler-shifted spectra of the I / Q signals and estimated the radial electric field in an electron cyclotron heated (ECH) plasma.